Common or independent? The debate over regulations and standards for water reuse in Europe - Fawell, John; Le Corre Pidou, Kristell; Jeffrey, Paul (Elsevier, 2016)
Although unplanned water reuse has been practised across Europe for decades, multiple stresses on water supply and demand over recent years have led to the development of many planned reuse schemes. Despite this development, the legislative and regulatory regimes required to underpin a growing water reuse sector have arguably failed to emerge. The reasons for this and the cases for and against pan-European water reuse regulations are explored and debated. The conclusions highlight several challenges for politicians and policy makers if appropriate regulatory systems and water quality standards are to be provided which support the embryonic European water reuse sector.
Keywords: Water quality; water reuse; Europe; regulations; standards; governance